1987
DOI: 10.1172/jci112805
|View full text |Cite
|
Sign up to set email alerts
|

Changes in amount and intracellular distribution of androgen receptor in human foreskin as a function of age.

Abstract: To provide insight into the factors that control growth of the penis we measured the amount and intracellular distribution of specific high affinity androgen receptor in foreskins obtained at circumcision from 49 males varying in age from newborn to 59 yr. Total (cytosolic plus nuclear extract) androgen receptor decreased from -40 fmol/g tissue weight in newborn foreskins to -25 fmol/g by 1 yr of age. The amount of receptor rose in childhood to '-180 fmol/g in the late teenage years and fell thereafter to -204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 18 publications
2
8
0
3
Order By: Relevance
“…Gynaecomastia in the adult male is a sensitive indicator of disturbed androgen/oestrogen ratios or of impaired androgen action mediated by AR (Wilson et al 1980). The concentration of AR begins to decrease in the normal male between the ages of 20-30 years, as shown strikingly in human foreskin fibroblasts (Roehrborn et al 1987). One hypothesis suggested by our findings is that adult onset androgen insensitivity observed in SBMA results from reduced AR mRNA and protein production compounded by normal AR attrition and the normal age-dependent decline in androgen levels (Zumoff et al 1982, Nahoul & Roger 1990.…”
Section: Reduced Ar Expression Accounts For Androgen Insensitivity Insupporting
confidence: 70%
“…Gynaecomastia in the adult male is a sensitive indicator of disturbed androgen/oestrogen ratios or of impaired androgen action mediated by AR (Wilson et al 1980). The concentration of AR begins to decrease in the normal male between the ages of 20-30 years, as shown strikingly in human foreskin fibroblasts (Roehrborn et al 1987). One hypothesis suggested by our findings is that adult onset androgen insensitivity observed in SBMA results from reduced AR mRNA and protein production compounded by normal AR attrition and the normal age-dependent decline in androgen levels (Zumoff et al 1982, Nahoul & Roger 1990.…”
Section: Reduced Ar Expression Accounts For Androgen Insensitivity Insupporting
confidence: 70%
“…Bélanger et al have already suggested that the observed decline in androgen levels could be partially compensated by an increase in steroidconverting enzymes in peripheral tissues, especially the 5a-reductase activity resulting in tissue dihydrotestosterone levels unaffected by aging (14). On the other hand, there is also evidence of decreased androgen tissue concentrations (1) and of reduced androgen sensitivity, with reports of decreased numbers of AR in various tissues in elderly men (37,38). However, up to now no practical and clinically useful biological marker of androgen activity at tissue level is available.…”
Section: Discussionmentioning
confidence: 99%
“…Em humanos, o número de receptores androgênicos do pênis normal aumenta na puberdade e diminui na idade adulta, variação essa também apresentada pela enzima 5-alfa-redutase (14). Estudos em ratos sugerem que a exposição precoce à testosterona (15) ou à di-hidro-testosterona (16) acelera a perda de receptores androgênicos, comprometendo o crescimento do pênis.…”
Section: Discussionunclassified